Evaluation of Rock Slope Deterioration Based on Granite and Schist Rock Slopes - R. Roslan; R.C. Omar; H. Taha; I.N.Z. Baharuddin; F. Ahmad (Lowland Technology International, 2020)
The problems of slope instability can be related to the terrainfactors and weather. In Malaysia, slope failures and landslidesare very common due to prolonged monsoon rainfalls. Theconsequences of slope instability can be hazardous to lifeincluding economic damages and costly repairs. The study wasaimed to determine the physical and mechanical properties ofthe rock slope material from selected sites. Several testsincluding field observations were performed to analyze theengineering characteristic and physical properties of this Schistrock slope and Granite rock slope. The rock samples wereclassified into various weathering grades based on variations inthese properties. Scan line methods were applied to obtain themeasurement data. Direct discontinuity surveys were carried outin interval of 10 m. Laboratory tests on the samples were donethat include two cycles of slake durability, Schmidt hammer test,point load test, petrography test, density test and direct shearbox test. The analysis on each rock types showed that theamphibolite Schist at Putrajaya has the highest rock strengthwith a uniaxial compressive strength (UCS) 487.97 Mpa which isclassified as extremely strong rock. By comparison, the UCSvalue of Granite was 267.28MPa and classified as strong rock